CÓMO OpTIMIzAR LA GESTIÓN pÚbLICA DEL pERÚ - Valeriano Ortíz, Luis Fernando (2013)
The national education system is the fundamental foundation for socio-economic development therefore requires a reengineering process for modernization in accordance with the advancement of science, technology and humanities, within the context of globalization.